Poles in Kaiser’s Army On the Front of the First World War - Kaczmarek, Ryszard (2020)
The book describes the fate of Poles in the German Imperial Army during the First World War. Poland did not exist for over a hundred years on the political map of Europe at that time, and the Poles had to fight for the opposite sides of the conflict: Germany, Austria, and Russia. In the German army, regiments recruited in Poznań, Upper Silesia, Masuria, and Eastern Pomerania were considered as “Polish.” They were sent to the Western front and participated in the great battles of Arras, Verdun, and the Somme. Poles were also present on the Eastern front, in the Balkans, on the Italian front, and even in the colonies. An important part of the forgotten history of Poles in the Kaiser’s army was the relationship between Polish soldiers and German officers. In regiments recruited on the Polish soil, it was common to use the Polish language, and from 1917 Poles deserted to the Polish Army formed in France.